Developing a conceptual framework of knowledge transfer in Malaysia E-Government IT outsourcing: an integration with transactive memory system - Abdul Hamid, Nor Aziati; Salim, Juhana (2012)
Knowledge transfer has attracted much attention to researchers and practitioners in recent years since knowledge transfer has been considered as a critical determinant of an organization’s capacity to confer sustainable competitive advantage. Despite extensive research on knowledge transfer issues, there is a dearth of research that has explicitly focused on the role of transactive memory in enabling intra-organizational knowledge transfer in information technology (IT) outsourcing context, particularly e-government IT outsourcing. Although the information systems literature has recently acknowledged the role of transactive memory plays in improving knowledge processes, most of the research is still in the basic concept of transactive memory which is emphasized more on the individual level of analysis or rather in the small group of people. Besides, most of related research was done in the lab based on the physical, virtual task or memory recall tasks. None of empirical work has been done in integrating TMS in outsourcing context since most researchers used interpretive approach. Therefore, this paper attempts to fill this gap by applying positivist approach through operalization of identified factors that significantly give positive impact towards knowledge transfer between the vendors to the Malaysian Public Agencies as the client.. Drawing on several theoretical streams, this paper will propose an integrated conceptual framework of interorganizational knowledge transfer with and integration of transactive memory system to facilitate knowledge transfer process between organizations which further can be used for research enhancement.